A critical analysis of drag force modelling for disperse gas-liquid flow in a pipe with an obstacle. (31st December 2021) - Tas-Koehler, Sibel; Liao, Yixiang; Hampel, Uwe
Highlights: The capabilities of different drag models under high turbulence /vortex flow conditions are shown. Impacts of turbulence effects on drag modelling are presented. A hybrid drag model is proposed for high turbulence flow conditions. Two-phase flow hydrodynamics under complex flow conditions is analyzed. Gas velocity and void fraction predictions are compared with experimental data. Abstract: The accuracy of the modelling of gas–liquid flows depends strongly on a suitable modelling of the interfacial forces. Among these, drag is dominant. Most drag models reported in the literature have been derived and validated only for laminar or low-turbulent flow conditions. In this study, we numerically evaluated several drag models from the literature for high-turbulent gas–liquid flow around an obstacle in a pipe that creates a distinct vortex region. We performed Computational Fluid Dynamics (CFD) simulations and compared the void fraction and gas velocity profiles with experimental data obtained by ultrafast X-ray computed tomography. We found that all models, except Schiller&Naumann and Feng, predicted the void fraction well compared to experimental data upstream of the obstacle, i.e., for a developed two-phase pipe flow with axial symmetry. However, the void fraction downstream is greatly overestimated by all models except those that appropriately consider the turbulence effects. Based on the results, a hybrid drag model is proposed that significantly improves the prediction of the void fraction.